Effect of Lateral and Stress‐Dependent Viscosity Variations on GIA Induced Uplift Rates in the Amundsen Sea Embayment. (2nd September 2021) - Blank, B.; Barletta, V.; Hu, H.; Pappa, F.; van der Wal, W.
Abstract: Accurate glacial isostatic adjustment (GIA) models are required for correcting measurements of mass change in Antarctica and for improving knowledge of the sub‐surface, especially in areas of large current ice loss such as the Amundsen Sea Embayment (ASE). Regionally, seismic and gravity data suggests lateral differences in viscosity (3D). Furthermore, mantle flow laws allow for a stress‐dependent effective viscosity which changes over time (3D‐s). In this study we investigate whether models with 3D/3D‐s have significant effects on the uplift in the region. We use a finite element model with composite rheology consisting of diffusion and dislocation creep, forced by an ice deglaciation model starting in 1900. We use its uplift predictions as synthetic observations to test the performance of 1D model inversion in the presence of viscosity variations. Stress‐dependent rheology results in lower viscosity beneath the load and a more localized uplift pattern. We demonstrate that the background stress from earlier ice load changes can both increase or decrease the influence of stress‐induced effective viscosity changes. For the ASE, fitting 1D models to 3D model uplift results in a best fitting model with viscosity that represents the average of a large area, while for 3D‐s rheology, local viscosity is more influential. 1D models are statistically indistinguishable from 3D/3D‐s viscosity with current GPS stations. However, 3D and 3D‐s models should be taken into account when accurate uplift and gravity rate patterns are needed, as uplift can differ up to 45% compared to 1D models in between existing GPS stations. Plain Language Summary: The Amundsen Sea Embayment (ASE) is a region in West‐Antarctica, which is losing mass upstream of the grounding line faster than almost any other region. Measurements of current ice mass change are obscured by uplift due to the melting of ice sheets in that past, termed glacial isostatic gdjustment (GIA). An accurate GIA model is required. The state‐of‐the‐art GIA model for the region assumes that the viscosity depth profile is the same everywhere. However, effective viscosity can change with location and under influence of stress which changes over time. In this study we use a finite element model to simulate GIA in the ASE and compare the simulated uplift from these models to an inverted 1D model. We show that when estimating average mantle viscosities, a simpler model would suffice. When higher stresses due to rapid deglaciation are taken into account in the description of the mantle flow, the uplift at the point of rapid deglaciation has a stronger rebound effect than previously considered. This would mean that the local ice mass loss obtained after correcting with current GIA models might also be bigger than what is obtained after correcting with simpler GIA models. Key Points: Uplift rates in the Amundsen Sea Embayment since 1900 are modeled with lateral and stress‐dependent viscosity changes (composite rheology) Including stresses from earlier ice loads can both increase and decrease stress‐induced viscosity changes 1D and 3D model uplift cannot be distinguished between using GPS sites but modeled uplift show significant differences in high uplift areas